Advanced BlackBerry 6 development - King, Chris 1972- (Apress, 2011)
BlackBerry devices and applications are selling by the millions. As a BlackBerry developer, you need an advanced skill set to successfully exploit the most compelling features of the platform. This book will help you develop that skill set and teach you how to create the most sophisticated BlackBerry programs possible. With Advanced BlackBerry 6 Development, you'll get a comprehensive look at the new features included with SDK 6, including the web and widgets SDK, the web browser, and more. You'll also learn how to take advantage of BlackBerry media capabilities such as the camera and video playback. The book also shows you how to send and receive text and multimedia messages, use powerful cryptography libraries, and connect with the user's personal and business contacts and calendar. Not only will you be learning how to use these APIs, but you'll also be building a program that takes full advantage of them: a wireless media-sharing app. Each chapter's lessons will be applied by enhancing the app from a prototype to a fully polished program. Along the way, you'll learn how to differentiate your product from other downloads by fully integrating with the new BlackBerry 6 operating system. Your app will run in the browser and within device menus, just like software that comes with the phone. You will even learn BlackBerry's new Web browser features, Web standards-based software development kit, and more. Once you are comfortable with writing apps, this book will show you how to take them to the next level. You'll learn how to move from running on one phone to running on all phones, and from one country to all countries. You'll additionally learn how to support your users with updates. No other resource compares for mastering the techniques needed for expert development on this mobile platform.